Kemampuan Organizational Citizenship Behavior dalam Memoderasi pengaruh Employee Engagement dan Islamic Work Ethic terhadap Kinerja Karyawan - Titania Oryza Sativa (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to determine how strong the influence of Organizational Citizenship Behavior (OCB) in Moderating the Effect of Employee Engagement and Islamic Work Ethics on Employee Performance of PT Sekolah Haji dan Umrah (SHU) Baitullah Central Java. In this study, a quantitative method was used using a questionnaire to 53 respondents who were permanent employees at all branches of PT Sekolah Haji dan Umrah (SHU) Baitullah Central Java using saturated sampling technique. Furthermore, the data that has been collected is then processed using the SPSS version 25 test tool. The test analysis used includes instrument test, classical assumption test, hypothesis testing and MRA (Moderated Regression Analysis) test. Based on the tests that have been carried out, the research results are obtained: 1) Employee engagement has a negative and significant effect on employee performance. 2) Islamic work ethics has a positive and significant effect on employee performance. 3) Organizational citizenship behavior is not able to moderate the effect of employee engagement on employee performance. 4) Organizational citizenship behavior is able to moderate the effect of Islamic work ethics on employee performance